Linear Preservers of Chain Majorization - P. Torabian (Journal of Mathematical Extension, 2008)
For (n×m matrices) X, Y ∈ Mnm(R)(= Mnm), we say X is chain majorized by Y and write X ≺≺ Y if X = RY where R is a product of finitely many T-transforms. A linear operator T : Mnm → Mnm is said to be a linear preserver of the relation ≺≺ on Mnm if X ≺≺ Y implies that T X ≺≺ T Y . Also, it is said to be strong linear preserver if X ≺≺ Y is equivalent to T X ≺≺ T Y . In this paper we characterize linear and strong linear preservers of ≺≺